Slum clearance and relocation: a reassessment of social outcomes combining short-term and long-term perspectives. Issue 2 (7th February 2019) - Kearns, Ade; Wright, Valerie; Abrams, Lynn; Hazley, Barry
Abstract: Housing research rarely takes a long-term view of the impacts of short-term housing changes. Thus, in studies of post-war relocation, narratives of 'loss of community' and 'dislocation' have dominated the debate for decades. This paper combines a 're-study' methodology with oral histories to re-examine the experience of relocation into high-rise flats in Glasgow in the 1960s and 1970s. We find that both the immediate and longer term outcomes of relocation varied greatly; while some people failed to settle and felt a loss of social relations, many others did not. People had agency, some chose to get away from tenement life and others chose to move on subsequently as aspirations changed. Furthermore, relocation to high-rise was not always the life-defining event or moment it is often depicted to be. Outcomes from relocation are mediated by many other events and experiences, questioning its role as an explanatory paradigm in housing studies.